Heath, Nixon and the Rebirth of the Special Relationship - Rossbach, Niklas H. author. aut Link
XIII, 293 p.
Keywords: This book reveals that 1969-74 was a crucial period for the special relationship. The Heath Government attempted to reverse Britain's decline as a great power by forging an American-European special relationship out of the Anglo-American relationship. Simultaneously the Nixon Administration tried to recoup the global position of the United States.